2013
DOI: 10.1177/2047487313494293
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the evaluation of excess exercise ventilation for prognosis assessment in pulmonary arterial hypertension

Abstract: Measurements of excessive exercise ventilation which consider all data points maximize the usefulness of incremental cardiopulmonary exercise testing in the prognosis evaluation of PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 42 publications
(183 reference statements)
0
37
0
Order By: Relevance
“…it aims to reflect how effectively O 2 is extracted from the atmosphere and taken into the body as exercise progresses. We recently found that a combination of increased sub-maximal exercise V9E as a function of carbon dioxide output (V9CO 2 ) and reduced O 2 delivery/utilisation (as suggested by shallow V9O 2 -work rate relationship) were independent predictors of negative outcome in PAH of mixed aetiology [7]. These findings prompted the hypothesis that OUES would combine the prognostic information provided separately by those variables, thereby being the single predictor of poor outcome in our cohort.…”
Section: To the Editormentioning
confidence: 70%
See 2 more Smart Citations
“…it aims to reflect how effectively O 2 is extracted from the atmosphere and taken into the body as exercise progresses. We recently found that a combination of increased sub-maximal exercise V9E as a function of carbon dioxide output (V9CO 2 ) and reduced O 2 delivery/utilisation (as suggested by shallow V9O 2 -work rate relationship) were independent predictors of negative outcome in PAH of mixed aetiology [7]. These findings prompted the hypothesis that OUES would combine the prognostic information provided separately by those variables, thereby being the single predictor of poor outcome in our cohort.…”
Section: To the Editormentioning
confidence: 70%
“…Additional sources of increasing nonmetabolic drive include excessive sympathetic drive, respiratory muscle weakness, ergoreceptor stimuli and increased pulmonary artery/right ventricle pressures [1][2][3][4][5]. These premises fully justify the notion that excessive V9E response to CO 2 (DV9E/DV9CO 2 slope) is a valuable marker of disease severity and progression in PAH [1][2][3][4][5]7].…”
Section: To the Editormentioning
confidence: 96%
See 1 more Smart Citation
“…This explains why these findings may be useful to assess disease severity when mechanical abnormalities do not play a major role in limiting exercise capacity, e.g. heart failure and pulmonary arterial hypertension [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Peak normalV˙normalO2/heart rate was calculated as peak normalV˙normalO2 divided by peak heart rate. Since previous studies show that normalV˙E/normalV˙CO2 slope calculated using the whole exercise period, as opposed to from the start of exercise to the ventilatory compensation point in patients with left‐sided heart failure and PAH, has better prognostic value, normalV˙E/normalV˙CO2 slope was determined by linear regression using the whole exercise period. OUES was determined by the slope of the regression line between log 10 minute ventilation normalV˙E ( x axis, L·min −1 ) and normalV˙normalO2 ( y axis, L·min −1 ) during the whole exercise period (normalV˙normalO2=a lognormalV˙E+b;a=OUES).…”
Section: Methodsmentioning
confidence: 99%